Kemampuan Siswa Kelas V dalam Menyelesaikan Soal Materi Pengelolahan Data di SD Negeri Curug II - Unaenah, Een; Anggraeni, Ani Nur; Wahyu, Rahma Rizkiya (ANWARUL, 2023)
This study aims to describe the understanding of grade 5 students in learning data processing and to identify the types of errors that are often made by students. This study originates from the law of the Ministry of Learning of the Republic of Indonesia, No. 57 in 2014 on demonstrating essential skills of mathematics in specialization development, communication and life adjustment. This study used full-time and student checks of 34 students from SD. Data was collected through interviews, questionnaires and tests. Data processing includes making tables, line diagrams and bar diagrams. The results of the study show that students' understanding of data processing still needs to be improved. Common errors are conceptual errors, data usage errors, data interpretation errors, technical and input errors. Errors in the conclusions listed are common errors. Data processing education should be improved by providing a better understanding of basic data processing concepts and teaching students the proper way to use, interpret, and present data. It is also important to choose learning methods that are interactive, relevant and interesting to students. This research helps improve computer science education in grade 5 elementary schools and informs more effective learning efforts to improve students' understanding of mathematics.